A Review on Mannich Base Derivatives Some of Natural Compounds: Antimicrobial Activities - Eva Siburian; Hayun Hayun; Herman Suryadi (Eduvest - Journal of Universal Studies, 2025)
This review explores the synthesis and antimicrobial potential of Mannich base derivatives derived from various natural compounds. The Mannich reaction, a versatile method in organic synthesis, enables structural modification of bioactive compounds to enhance their pharmacological properties, particularly antimicrobial activities. This study systematically reviews recent literature on the design, synthesis, and biological evaluation of these derivatives against bacterial and fungal pathogens. The findings demonstrate that Mannich base derivatives exhibit improved efficacy through multiple mechanisms of action, such as inhibition of cell wall synthesis, protein synthesis, and membrane disruption. The review highlights the relevance of Mannich-based structural optimization as a promising strategy in the development of novel antimicrobial agents.